Population dynamics and economic growth: Should we adopt different frameworks for poor and rich countries? - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2011)
From the canonical model of Becker onward, models of population dynamics have been based on assumptions which fit the family structure of developed countries. The aim of this paper is to develop a framework that fits the family structure of poor countries. The building blocks of the model incorporate elements essential to the determination of population dynamics in poor countries, i.e., child labor, intergenerational flows from children to parents, and the effects of child labor on children's health. The main result of this paper is that the correlation between economic growth and fertility rates runs in inverse directions for poor and rich countries.
Keywords: J13; O11; O16; O40; 330; child labor; health deterioration; intergenerational transfers; fertility rates; Kinderarbeit; Gesundheitsrisiko; Intergenerationale Übertragung; Familienplanung; Fertilität; Wirtschaftswachstum; Familienökonomik; Welt